Below‐ground ecosystem engineers enhance biodiversity and function in a polluted ecosystem. Issue 8 (31st May 2022) - Bugnot, Ana B.; Gribben, Paul E.; O'Connor, Wayne A.; Erickson, Katherine; Coleman, Ross A.; Dafforn, Katherine A.
Abstract: Many important ecosystem functions are underpinned by below‐ground biodiversity and processes. Marine sediments, one of the most abundant habitats on earth, are essential to the mineralisation of organic matter. However, they are increasingly polluted by urban activities leading to the loss of biodiversity and the functions they provide. While traditional sediment remediation strategies are focussed on microbial and engineering solutions, we propose that the reintroduction of below‐ground ecosystem engineers (bioturbators) is important to rehabilitate polluted sediments and drive recovery of their functions in urban coastal ecosystems. We tested this notion by introducing bioturbators to nutrient polluted sediments to assess their survival, as well as their capacity to drive biodiversity and oxygenation and their potential to remediate nutrient pollution. Polychaete worms Diopatra aciculata and clams Katelysia sp. were added to mesocosms (ex‐situ), and the worms also added to experimental plots in‐situ. Potential for remediation was assessed with measures of nutrient content. All animals survived when introduced to polluted sediments and showed no evidence of sub‐lethal effects. Worms oxygenated sediments and reduced organic matter content by up to 50% in‐situ. The worms also drove shifts in the receiving communities at all locations and increased the number of taxa at one location. On the other hand, the effects of clams were variable, showing opposite effects in organic matter content at different sites and levels of pollution. Synthesis and applications . Global seafloor habitats are becoming increasingly degraded and novel strategies that combine biodiversity restoration with remediation are urgently needed to return function. Tube‐building bioturbators can stimulate nutrient processing in sediments proving multiple functional outcomes, but these effects are dependent on the receiving environment. In areas with medium levels of pollution, they can kick‐start recovery in a feedback loop whereby bioturbation increases oxygenation and nutrient remediation, shifting sediment biodiversity and contributing to further recovery. This can drive long‐term changes in sediment communities, particularly in urban areas where unvegetated sediments are conspicuous. Abstract : Global seafloor habitats are becoming increasingly degraded and novel strategies that combine biodiversity restoration with remediation are urgently needed to return function. Tube‐building bioturbators can stimulate nutrient processing in sediments proving multiple functional outcomes, but these effects are dependent on the receiving environment. In areas with medium levels of pollution, they can kick‐start recovery in a feedback loop whereby bioturbation increases oxygenation and nutrient remediation, shifting sediment biodiversity and contributing to further recovery. This can drive long‐term changes in sediment communities, particularly in urban areas where unvegetated sediments are conspicuous.